Long Intergenic Noncoding RNA 00511 Acts as an Oncogene in Non-small-cell Lung Cancer by Binding to EZH2 and Suppressing p57 - Cheng-Cao Sun; Shu-Jun Li; Guang Li; Rui-Xi Hua; Xu-Hong Zhou; De-Jia Li (Elsevier, 2016)
Long noncoding RNAs (lncRNAs) play crucial roles in carcinogenesis. However, the function and mechanism of lncRNAs in human non-small-cell lung cancer (NSCLC) are still remaining largely unknown. Long intergenic noncoding RNA 00511 (LINC00511) has been found to be upregulated and acts as an oncogene in breast cancer, but little is known about its expression pattern, biological function and underlying mechanism in NSCLC. Herein, we identified LINC00511 as an oncogenic lncRNA by driving tumorigenesis in NSCLC. We found LINC00511 was upregulated and associated with oncogenesis, tumor size, metastasis, and poor prognosis in NSCLC. Moreover, LINC00511 affected cell proliferation, invasiveness, metastasis, and apoptosis in multiple NSCLC cell lines. Mechanistically, LINC00511 bound histone methyltransferase enhancer of zeste homolog 2 ((EZH2, the catalytic subunit of the polycomb repressive complex 2 (PRC2), a highly conserved protein complex that regulates gene expression by methylating lysine 27 on histone H3), and acted as a modular scaffold of EZH2/PRC2 complexes, coordinated their localization, and specified the histone modification pattern on the target genes, including p57, and consequently altered NSCLC cell biology. Thus, LINC00511 is mechanistically, functionally, and clinically oncogenic in NSCLC. Targeting LINC00511 and its pathway may be meaningful for treating patients with NSCLC.